Computational investigation of natural compounds as potential main protease (Mpro) inhibitors for SARS-CoV-2 virus - Patel, Chirag N; Jani, Siddhi P; Prasanth Kumar, Sivakumar; Modi, Krunal M; Kumar, Yogesh (Computers in biology and medicine, 2022)
The coronavirus disease 2019 (COVID-19) pandemic caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) is significantly impacting human lives, overburdening the healthcare system and weakening global economies. Plant-derived natural compounds are being largely tested for their efficacy against COVID-19 targets to combat SARS-CoV-2 infection. The SARS-CoV-2 Main protease (Mpro) is considered an appealing target because of its role in replication in host cells. We curated a set of 7809 natural compounds by combining the collections of five databases viz Dr Duke's Phytochemical and Ethnobotanical database, IMPPAT, PhytoHub, AromaDb and Zinc. We applied a rigorous computational approach to identify lead molecules from our curated compound set using docking, dynamic simulations, the free energy of binding and DFT calculations. Theaflavin and ginkgetin have emerged as better molecules with a similar inhibition profile in both SARS-CoV-2 and Omicron variants.
Keywords: Main proteases (M(pro)); pandemie; farmakoterapie COVID-19; proteasy; DFT calculation; lidé; Peptide Hydrolases; Dynamics simulation; SARS-CoV-2; Omicron; COVID-19 Drug Treatment; Binding free energy; Pandemics; Humans